MEMBANGUN TOLERANSI DALAM MASYARAKAT MAJEMUK TELAAH PEMIKIRAN NURCHOLIS MADJID - Ngainun Naim (Harmoni, 2013)
Philosophically, human can be called as dialogical creature. The way to apply dialogical consciousness among human being needs the seriousness. In a daily life, dialogical consciousness will give big impact to the human behavior. In this case, tolerance has an important position to create this condition. According to Nurcholish Madjid, tolerance in Islamic religion is something to be based. Unity of God becomes the main destination. Tolerance can develop well to the human being having understanding and openness. The application of tolerance will create strong civil society. It is also appropriate with the pluralism of Indonesian society.